Sissy insurgencies : a racial anatomy of unfit manliness - Ross, Marlon Bryan, 1956- (Duke University Press, 2022)
"Marlon B. Ross explores the figure of the sissy as central to how Americans have imagined, articulated, and negotiated black masculinity from the 1880s to the present."--